Robert Mapplethorpe. - Mapplethorpe, Robert; Weiermair, Peter (Frankfurt : Frankfurter Kunstverein, 1981)
Fonds Suzan Daniel (FSD)
Fotoboek uitgegeven n.a.v. tentoonstelling Frankfurter Kunstverein van 10 april tot 17 mei 1981
Duits
Brochure